1999
DOI: 10.1056/nejm199902253400806
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Race and Sex on Physicians' Recommendations for Cardiac Catheterization

Abstract: Our findings suggest that the race and sex of a patient independently influence how physicians manage chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
1,022
10
18

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,707 publications
(1,071 citation statements)
references
References 39 publications
21
1,022
10
18
Order By: Relevance
“…Contrary to our findings, they saw increased disparity in limb loss for black patients living in wealthier areas even though there was an overall increase in the likelihood of receiving revascularization for all patients residing in wealthier ZIP codes 7. Provider bias, influenced by race, in the management of cardiovascular disease has been described in the literature 30, 31. We found that black patients had lower rates of prescriptions for statins and antiplatelet agents in our cohort compared with white patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, they saw increased disparity in limb loss for black patients living in wealthier areas even though there was an overall increase in the likelihood of receiving revascularization for all patients residing in wealthier ZIP codes 7. Provider bias, influenced by race, in the management of cardiovascular disease has been described in the literature 30, 31. We found that black patients had lower rates of prescriptions for statins and antiplatelet agents in our cohort compared with white patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Even the most well-meaning and egalitarian physicians may have stereotypes or biases based on a patient's demographic status (Burgess, Fu & Van Ryn, 2004;Van Ryn, Burgess, Malat & Griffin, 2006). Racial bias, in particular, has been implicated in research showing that some physicians associate more negative attributes (e.g., non-compliant, less intelligent, more likely to abuse drugs and alcohol) to minority and less educated patients (Van Ryn & Burke, 2000), perceptions that in turn may affect physicians' informativeness (Amir, 1987) and medical decision-making (Krupat, Irish, Kasten, Freund, Burns, Moskowitz et al 1999;Schulman, Berlin, Harless, Kerner, Sistrunk, Gersh et al 1999). Such findings have led some to explore whether demographic concordance between physician and patient may facilitate better relationships and more positive health care interactions because the physician and patient have some element of shared identity.…”
Section: Conceptual Framework: An Ecological Approachmentioning
confidence: 99%
“…Furthermore, the receipt of cardiac catheterization and specialty care for patients presenting at nonmetropolitan hospitals without these services often requires transfer to centers located in metropolitan areas. Financial barriers,7, 8 intrinsic physician bias,16 and other factors may result in differential receipt of these services based on area median income. Few studies have examined specifically whether location of care modifies the association among area median income and access to cardiac catheterization and outcomes of ACS 9.…”
Section: Introductionmentioning
confidence: 99%